“Tweeting During Emergencies”: The Egyptian Ministry of Health Twitter Communication Strategy Under the Umbrella of the Crisis and Emergency Risk Communication Model (CERC) CASE STUDY: COVID-19 Pandemic - ElGohary, Pakinam (AUC Knowledge Fountain, 2023)
This research investigates using the Crisis and Emergency Risk Communication Model (CERC) for COVID- 19 communication by analyzing the content of Twitter messages posted by the Government of Egypt through the Egyptian Ministry of Health (MOHP). It further examines how official communicators and institutions utilize social media to contact the public during emergencies like the COVID-19 pandemic, highlighting critical strategies of recommendations. Crisis and Emergency Risk Communication (CERC), a five-staged theory, recommends a set of messaging and pertained communication characteristics to implement at each stage of the identified following stages: (1) “Pre-crisis, (2) Initial event, (3) Maintenance, (4) Resolution, and (5) Evaluation”. The Egyptian Ministry of Health succeeded in applying most, if not all, of the recommended messaging and communication characteristics with varying frequency levels; however, it did not comply with the recommended order of stages while applying these characteristics. Throughout the study, the MOHP’s tweets achieved each CERC principle. Like the CERC characteristics, all CERC principles were also achieved at varying frequency levels. This study also showed different levels of engagement with different CERC characteristics.